SISTEM PEMBUATAN BARCODE BARANG BERBASIS WEB PADA PT. CHUGOKU PAINTS INDONESIA - Ilamsyah Ilamsyah; Dona Listyanto Pangestu; Reza Zulian Pramana (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2016)
T.CHUGOKU PAINTS INDONESIA is a private company engaged in the manufacture of paints for industrial needs with the quality and formulation of Japan. A company that produces various types of paint for the plant. Ranging from the manufacture of special paint ships, power plants, steel and wood to meet customer needs in the field of industri.di where this company. Still barcode creation process is still manual and not integrated with a web so that it can facilitate the manufacture and control in the manufacture of barcode goods. Technological developments in the computer system enables improvement in all branches of production, such as the manufacture of goods still manual barcode, barcode creation process is slow and depends on the conditions. Due to the manufacture of barcode system that has been using the web will bring an ease to the company to be able to indulge easily. The use of computer systems is very important in supporting a company's development in today. Computer use can also facilitate and expedite the processing, storing important data even as the company's own material. The methodology used is a method ofresearch that began by conducting surveys, interviews, and analysis according to the theory of the books that can support the design manufacture goods barcode. From these results, PT. CHUGOKU PAINTS INDONESIA can improve produtivitas and performance of the company to be competitive in the business world that is increasingly tight. In addition, with this research the company has a better ability to present and future.